Implementation and Analysis of Quadrature Amplitude Shift Keying Modulation Using SDR Devices for Wireless Communication Systems - Rizkha Rochmatika; Jeffri Pratama; Slamet Mulyadi; Abu Hasan; Irfan Mujahidin; Muhlasah Novitasari Mara; Filda Hulwani Dewi (JAICT, 2026)
This research aims to implement and analyze the performance of Quadrature Amplitude Shift Keying (QASK) modulation in wireless communication systems using Software Defined Radio (SDR) devices. This research uses ADALM-PLUTO as the transmitter and RTL-SDR as the receiver, with signal processing performed through GNU Radio software. The main focus of this research is to evaluate the implementation of 4-QASK modulation in wireless data transmission at several different frequencies (300 MHz, 500 MHz, 1 GHz, and 1.5 GHz) and different distances (1 meter to 5 meters), as well as to measure transmission quality using the Packet loss and Received Signal Strength Indicator (RSSI) parameters. The test results show that this system is capable of transmitting data with good quality, with RSSI values ranging from 51.41 dBm to -62.59 dBm, indicating good to very good signal quality. This test also showed that the further the distance between the transmitter and receiver, the lower the signal reception quality, especially at higher frequencies, indicating a significant influence of distance and frequency on the received signal strength. Based on the results obtained, it can be concluded that QASK modulation using SDR, particularly 4-QASK, is effective in wireless communication with good performance at short to medium distances.